MULTIFACETED RELATIONSHIP BETWEEN ACCOUNTING, INNOVATIVE ENTREPRENEURSHIP, AND KNOWLEDGE ... MANAGEMENT : theoretical concerns and empirical ins. - SPAN, ROSANNA (Emerald points, 2019)
The book recognises three compartmental debates surrounding control, innovative entrepreneurship, and knowledge management which need to be integrated to support the entrepreneurial adventure. Acknowledging a need to build a bridge between theory and practice, the book provides a rich empirical analysis to support the theoretical issues raised.